Dose-Response Effects of Liquid Organic Fertilizer Substitution on Growth, Yield, and Nitrate Accumulation of Lettuce (Lactuca sativa L.) in NFT and DWC Hydroponic Systems - Chiska Nova Harsela; Indi Millatul Maula (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The growing reliance on synthetic inorganic nutrient solutions in hydroponic agriculture poses significant ecological, economic, and food safety concerns, necessitating the evaluation of sustainable organic alternatives that can maintain crop productivity while reducing chemical inputs. Objective: This study determined the optimal LOF substitution ratio for inorganic nutrient solutions in Nutrient Film Technique (NFT) and Deep Water Culture (DWC) hydroponic systems, evaluating effects on plant growth, yield, leaf nitrate accumulation, and solution chemistry in lettuce (Lactuca sativa L.). Methods: A 5 × 2 factorial experiment was conducted with five LOF substitution levels (0%, 25%, 50%, 75%, 100%) across two hydroponic system types (NFT and DWC), using lettuce (Lactuca sativa L. cv. Grand Rapids). Parameters measured included plant height, leaf area index, fresh weight, dry weight, root length, chlorophyll content (SPAD), leaf nitrate concentration, and nutrient solution EC, pH, and dissolved oxygen. Results: The 75% LOF + 25% inorganic treatment (T2) produced statistically equivalent fresh weight (142.3 ± 7.1 g/plant, NFT) to the full inorganic control (148.7 ± 6.4 g/plant; p = 0.312), while reducing leaf nitrate by 34.2% and fertilizer input costs by 50.3%. Full LOF (100%) significantly reduced yield by 39.9% but achieved the greatest nitrate reduction (57.7%). Conclusion: Substituting 75% of inorganic nutrient solution with LOF is agronomically viable, economically advantageous (50.3% cost reduction), and improves food safety in hydroponic lettuce production, supporting circular bioeconomy principles in precision-managed soilless cultivation.